Reconstruction of norm in selection system of Constitutional Court judge candidates from the perspective of the paradigm of Prophetic Law - Lutfi, Mustafa; Ibrahim Nur, Asrul (Legality : Jurnal Ilmiah Hukum, 2022)
This article aimed to discuss the selection system of Constitutional Court Judges in Indonesia. The standardization of the recruitment system in the selection of candidates for Constitutional Court judges performed by DPR, the President, and the MA has varied due to multi-interpretations of the provisions of Article 20 (1) & (2) of Constitutional Court Law, contrary to the fact that the Third Amendment to Constitutional Court Law sets forth the mandate to selection committees. The model of the recruitment system has not been constitutionally optimal, while the process mechanism should meet transparency (involving public knowledge), participation (getting the public involved in every process), objectivity (competency-based), and accountability. However, several recruitment practices have overlooked those principles, urging further evaluation of the recruitment to take place comprehensively. One gate system in the recruitment with the assistance of the selection committees seems to be inevitable and simultaneously serves as the solution to reconstruct the system into a more standardized one in the time to come. Moreover, the selection committees must be true statesmen since they hold the authority to verify and select other statesmen as the candidates for the recruitment. The involvement of credible, professional, objective, transparent, and participative selection committees is expected to help achieve legal objectives and intent as wished by the constitution and to bring about the spirit of the prophetic law that serves as the core of the subject matter.